The Importance of Classifying an Asset as Belonging to the Public Domain - Catalina-Georgeta Dinu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2024)
According to the special Law no. 165/2013 regarding the measures to complete the restitution process, the Local Land Fund Commissions drew up the validation proposal from Annex no. 29, in Annex 23, meaning that the County Land Fund Law Enforcement Commissions revoked the decisions that contained the recognition of the right to property on the land that was illegally taken by the communist regime and entered the state property. So, this type of land can be unavailable for the former expropriated owner, in favour of the state? On the other hand, Romania adopted new regulations which complete Law no. 222/2017 with a provision allowing the alienation, by donation to third parties, of a Patriot system owned by the Romanian state. This research wants to highlight two situations where the delimitation between public and private domain has practical importance.